Development of BeiDou Satellite‐Based Augmentation System. Issue 2 (22nd May 2021) - Cheng, Liu; Weiguang, Gao; Bo, Shao; Jun, Lu; Wei, Wang; Ying, Chen; Chengeng, Su; Shuai, Xiong; Qun, Ding
Abstract: China is developing its BeiDou Satellite‐Based Augmentation System (BDSBAS) in accordance with international standards, and it has provided initial Single Frequency (SF) and Dual‐Frequency Multi‐Constellation (DFMC) services since July 2020. This paper gives a comprehensive introduction to BDSBAS from the aspects of its general design, system time datum, coordinate reference system and signal characteristics. The performance requirements and internationalization endeavors of BDSBAS also are presented. Additionally, the initial performance tests of BDSBAS SF service had been carried out based on the first two BDSBAS Geosynchronous Earth Orbit (GEO) satellites, including the quality of signal‐in‐space, and initial accuracy, integrity and availability. The results show that the characteristics of BDSBAS signal‐in‐space can well meet the requirements of the International Civil Aviation Organization (ICAO), and the initial performance of BDSBAS SF service can basically meet the requirements of Approach with Vertical guidance I (APV‐I). Finally, before the application of BDSBAS services into civil aviation uses, testing and certification will be organized by the Civil Aviation Administration of China (CAAC) and carried out in three steps. In the future, China will continue to promote the development of BDSBAS in a steady manner in order to provide aviation integrity services compatible with the ICAO standards in China and the surrounding areas as soon as possible.